+0  
 
0
554
2
avatar+1016 

Simplify.

−6i−44−−−−√

 

Enter your answer, in simplest radical form, in the box.

 Jan 17, 2018
 #1
avatar+10110 
0

Now it is correct.

laugh

 Jan 17, 2018
edited by Omi67  Jan 17, 2018
 #2
avatar+17746 
0

-6i · sqrt( -44 )

 

Since sqrt( -44 )  =  i · sqrt( 44 )

                           =  i · sqrt( 4 ) · sqrt( 11 ) 

                           =  i · 2 · sqrt( 11 ) 

                           =  2i · sqrt( 11 ) 

 

-6i · sqrt( -44 )  =  -6i · 2i · sqrt( 11 ) 

                         =  -12 · i2 · sqrt( 11 ) 

 

Since  i2  =  -1:

                         =  -12 · -1 · sqrt( 11 )

                         =  12· sqrt( 11 )

 Jan 17, 2018

24 Online Users

avatar
avatar
avatar
avatar
avatar
avatar